Assessment of accuracy of IKONOS image map, traditional orthophoto map and conventional line map of Kathmandu valley: A pilot study - Kayastha, Durgendra Man; Chhatkuli, Raja Ram; Paudel, Jagat Raj (Journal on Geoinformatics, Nepal, 2004)
IKONOS image mapping is being considered a possible replacement to the traditional mapping in many countries due to their ease of access to current data and their potential high resolution. Survey Department of His Majesty's Government completed traditional orthophoto mapping of all urban and semi-urban areas of the country. The 1:5000 monochrome orthophoto maps of Kathmandu valley were completed in 2003. In 2002, as a test, production of a near natural colour image map at 1:5000 scale of a part of Kathmandu valley based on IKONOS data was carried out. A conventional line map plotting of the same area at 1:5000 was also preapared. The objective of the pilot project was to access the geometric accuracy and the information content of these maps. The details of the study and their results are underlined. The findings of the study helps to explain whether IKONOS image map can replace conventional orthophoto map at 1:5000 for urban areas of Nepal like Kathmandu.